The Importance of Entrepreneurship Education in Preparing the Young Generation to Face Global Economic Challenges - Mahmudin, Tono (ADMAN: Journal of Contemporary Administration and Management, 2023)
Entrepreneurship education plays a crucial role in preparing the younger generation to face the increasingly complex challenges of the global economy. The era of globalization and technological advancements has significantly transformed the business landscape, necessitating innovative entrepreneurial skills and thinking to compete effectively. The aim of this research is to analyze the importance of entrepreneurship education in preparing the younger generation for the challenges of the global economy. The approach involves a comprehensive review of relevant literature through qualitative analysis, with the objective of obtaining a thorough understanding of the subject from 2005 to 2023. The study results indicate that in the continually changing and complex context of the global economy, entrepreneurship education proves to be highly essential in preparing the younger generation for existing challenges. Entrepreneurship education not only provides a foundation of business knowledge but also develops entrepreneurial skills and business ethics values. The younger generation, having undergone this education, gains an advantage in identifying and seizing global business opportunities, as well as the ability to manage risks and face economic changes with composure. The significance of creativity, innovation, and social responsibility in entrepreneurship curriculum also emphasizes that this education is not only about business success but also about positive impacts on society and the environment.